Safety and efficacy of general anesthesia versus spinal anesthesia in percutaneous nephrolithotomy - Srinivasa VY,; Kailash P Dev,; Anjali Kumari B, (Asian Journal of Medical Sciences, 2024)
Background: Percutaneous nephrolithotomy (PCNL) is the preferred treatment for the removal of large kidney stones, sized >20 mm. However, there is still an ongoing debate concerning the best anesthesia for PCNL. Aims and Objectives: The objective of this study was to assess and compare the efficacy and safety of spinal anesthesia (SA) versus general anesthesia (GA) in PCNL. Materials and Methods: A prospective randomized study included eighty-two patients who were enrolled to receive either SA or GA for PCNL. The study assessed patients’ characteristics, vital parameters, requirements for additional analgesia, and patient satisfaction. In addition, intraoperative and post-operative complications were documented. Patients’ satisfaction was also analyzed. Results: In both groups, the vital parameters were consistently maintained at safe levels during the procedures. Patients in the SA group exhibited a lower analgesia consumption on the 1st post-operative day compared to the GA group (P<0.05). Post-operative hypotension was higher in the SA group than in the GA group (17% vs. 7%). Patients in the GA group reported higher patient satisfaction scores than the SA group (mean 4.39+0.59 vs. 3.81+0.64). Conclusion: Both SA and GA are safe and effective in PCNL. SA is associated with fewer complications and reduced postoperative analgesia consumption. However, GA tends to offer higher satisfaction levels for patients. Each method of anesthesia has its own advantages and disadvantages. The final choice between general and SA should be based on the patient’s condition and surgical team preference.